Health promotion: an instituing element? - Fernandez, Juan Carlos Aneiros; Andrade, Elisabete Agrela de; Pelicioni, Maria Cecília Focesi; Pereira, Isabel Maria Teixeira Bicudo (Saúde e Sociedade, 2008)
The article includes, in the discussion about health promotion results, an epistemological argument, considering the contemporary context of changes of which it is part and expression. The suspicion concerning the project of Modernity is emphasized, as a result of growing uncertainties or unfulfilled promises. In addition, the attempts to solve the conflict between determination and autonomy are also highlighted. Both aspects are considered as sensible questions regarding a rupture of the ways of knowing in contemporariness. The article proposes to consider social dynamics, approaching it as the union and tension of concluded history and ongoing history, so as to better understand the reach and results of health promotion. The conclusion is that health promotion must continue the search for the development of increasingly effective actions, but it must do it without abdicating the possibility of remaining close to the free social energy, which is the characteristic of the instituting element of historical production.